Pleistocene sedimentary facies of the Gran Dolina archaeo-paleoanthropological site (Sierra de Atapuerca, Burgos, Spain). (17th March 2017) - Campaña, I.; Benito-Calvo, A.; Pérez-González, A.; Ortega, A.I.; Bermúdez de Castro, J.M.; Carbonell, E.
Abstract: Gran Dolina is a cavity infill of the Sierra de Atapuerca, containing three important Early and Middle Pleistocene archaeo-paleontological layers, including hominid bones, fauna and lithic remains. Due to the relevance of this site to understand human evolution in Europe, it is essential to define in detail the sedimentary processes and environments associated with the archaeological remains. Gran Dolina has a 19 m thick sedimentary infill divided into 11 lithostratigraphic units. In this work, we describe the sedimentary facies of the Early and Middle Pleistocene units and we update its stratigraphy. For that purpose, we have studied the stratigraphic excavation profiles available, where we have combined field observations with laboratory sedimentary analysis (sieving, laser diffraction, and image analysis) to characterize the texture and structure of the sediments. Through these studies, 19 sedimentary facies have been distinguished, grouped as sediment gravity flow facies, fluvial facies and autochthonous facies. The facies associations indicate two main trends in the allochthonous sequence. During the Early Pleistocene (TD4–TD7), the cavity acted as a stream sink, where channel and floodplain facies migrated along the sequence, and were interbedded with lateral gravity sediment flows. On the other hand, the Middle Pleistocene sequence between TD7 and TD10 is dominated almost exclusively by gravity flows. At least three main entrances have been inferred from input directions of the sediments, which changed over time. Sediment characteristics have allowed us to preliminarily infer environmental conditions around the cavity.